Philosophy of religion and art (Cambridge Scholars Publishing, 2021)
"This volume serves to fill a lacuna in the literature of the analytic philosophy of religion by relating key philosophical themes to broader aspects of the humanities, such as visual art, literature, and pop culture studies. The essays here range from discussions of the nature of art and religious experience, to the role of art in religious dialogue, and the function of narrative in religious discourse, as well as cultural media and artistic and phenomenological experience."--